DISPERSION MODELING OF NATURAL RADIONUCLIDES 238U, 232TH, 226RA, 40K IN MURIA COASTAL WATERS - Dwi Purwantoro Sasongko; S upriharyono; Wahyu Setiabudi (JOURNAL OF COASTAL DEVELOPMENT, 2012)
Dispersion modeling of natural radionuclides 238U, 232Th, 226Ra, 40K in Muria coastal waters has been carried out in sea water and sediment surounding Tanjungjati B coal-fire power plant and nuclear power plant site’s candidate by applying the hydrodynamics model of unsteady 2-dimensional flexible grid. Oceanography data collecting of bathimetry, current, wave, tide and wind had been carried out on May 28, 2006 until June 2006. Updating data was conducted on April 27 up to April 29, 2011 by using Acoustic Doppler Current Meter Profiler (ADCP) to measure the wave and subsurface current with duration of 2x24 hours. Sea water and sediment samples were collected on April 22, 2011 in six locations (surounding Tanjungjati CPP) and on April 23, 2011 in 10 locations (surounding NPP site’s candidate). Samples were analyzed at Research Center for Safety Technology and Radiation Metrology Laboratory, National Nuclear Energy Agency, Jakarta on May 2011 until September 2011 by using spectrometri-γ analysis. Result shows that it can be identified and measured the natural radionuclides of 238U, 232Th, 226Ra, 40K in sea water and sediment. The study can be justified that natural radionuclides of 238U, 232Th, 226Ra, 40K was leachated from fly ash and bottom ash of coal burned Tanjungjati CPP to sea water. The hiyrodynamics model of unsteady 2-dimensional fexible grid by using CD Oceanography software for current plotting, ArcView GIS 3.3 software for bathimetric contouring and SMS 8.1 software for modeling of natural radionuclides dispersion in coastal waters one can applied for radionuclides dispersion of 238U, 232Th, 226Ra, 40K in Muria coastal waters.